(untitled) (Texas Journal of Medical Science, 2024)
This article talks about the sanctity of the family, traditions typical of Uzbek families, family etiquette among elementary school students. The rich historical, cultural and educational heritage, traditions and values of our people were discussed in the issues of education and morals. Also, based on the teachings of our great thinker, attention was paid to the most important issues of family relations, the duty of parents in the family and their responsible approach in this regard.